SYNTHESIS AND ANTIBACTERIAL ACTIVITY OF SOME NEW PYRIDINYL/QUINAZOLINYL/AZETIDINONYL/THIAZOLIDINONYL TRIAZOLES - INDU SINGH; HEMLATA KAUR; SUNIL KUMAR; ARUN KUMAR; ASHOK KUMAR (International Journal of Pharma and Bio Sciences, 2010)
A series of N-(6-bromo-2-methyl-4-oxoquinazolin-3(4H)-yl)-2-(4-(3-chloro-2-(substitutedphenyl)-4- oxoazetidin-1-yl)-5-(pyridin-4-yl)-5-thio)acetamido-1,2,4-triazoles (5a-5g) have been prepared by the condensation of 6-bromo-2-methyl-4-oxoquinazolin-3(4H)-yl-2-(4-(substitutedbenzylideneamino)-5-(pyridin-4- yl)-3-thio)acetamido-1,2,4-triazoles (4a-4g) with chloroacetyl chloride in presence of trimethylamine. N-(6- bromo-2-methyl-4-oxoquinazolin-3(4H)-yl)-2-(4-(2-(substitutedphenyl)-4-oxothiazolidin-3-yl)-5-(pyridin-4-yl)- 3-thio)acetamido-1,2,4-triazoles (6a-6g) have been synthesized by the reaction of compounds 4a-4g with thioglycolic acid in presence of anhydrous zinc chloride. All the newly synthesized compounds were screened for their antibacterial activity against S.aureus, E.coli, P.vulgaris, K. pneumoniae. Structures of all the compounds were established by elemental and spectral (IR, 1H NMR and Mass) analysis.